2019
DOI: 10.1021/acsomega.8b02546
|View full text |Cite
|
Sign up to set email alerts
|

Iron(III) Complexes for Highly Efficient and Sustainable Ketalization of Glycerol: A Combined Experimental and Theoretical Study

Abstract: The growing production of biodiesel as a promising alternative and renewable fuel led as the main problem the dramatic increase of its by-product: glycerol. Different strategies for glycerol derivatization have been reported so far, some more efficient or sustainable than others. Herein, we report a very promising and eco-friendly transformation of glycerol in nontoxic solvents and chemicals (i.e., solketal, ketals), proposing three new families of Fe(III) compounds capable of catalysing glycerol acetalization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 83 publications
1
28
0
Order By: Relevance
“…The activation energy using the liquid-phase ketalization of glycerol with acetone was also described in the literature (Esteban et al, 2015; Esposito et al, 2019). This current study found that an estimated E A , from the figure above is equal to 164.34 kJmol −1 and k 0 = 5.2678 * 10 28 (Con 1/2 .…”
Section: Resultsmentioning
confidence: 93%
“…The activation energy using the liquid-phase ketalization of glycerol with acetone was also described in the literature (Esteban et al, 2015; Esposito et al, 2019). This current study found that an estimated E A , from the figure above is equal to 164.34 kJmol −1 and k 0 = 5.2678 * 10 28 (Con 1/2 .…”
Section: Resultsmentioning
confidence: 93%
“…Glycerol, a highly functionalized molecule, was identified as one of the top twelve most important bio-based chemicals in the world by the US Department of Energy [1]. Glycerol has a wide range of applications, from the production of food additives to pharmaceuticals, cosmetics, personal care products and detergents, and it is also transformed into non-toxic solvents [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Homogeneous basic catalysis is the traditional industrial technology to obtain biodiesel and glycerol, (Scheme 4) also useful for several biobased product. [50] Its drawbacks are the difficult recovery of the catalyst, purification and disposal steps needed. Therefore, academic and industrial research focused on heterogeneous basic catalysts, mainly metal oxides.…”
Section: Transesterification Of Triglycerides For Biodiesel Synthesismentioning
confidence: 99%